2012
DOI: 10.1186/1477-7827-10-79
|View full text |Cite
|
Sign up to set email alerts
|

Late morfofunctional alterations of the Sertoli cell caused by doxorubicin administered to prepubertal rats

Abstract: BackgroundDoxorubicin is a potent chemotherapeutic drug used against a variety of cancers. It acts through interaction with polymerases and topoisomerase II and free radical production. Doxorubicin activity is not specific to cancer cells and can also damage healthy cells, especially those undergoing rapid proliferation, such as spermatogonia. In previous studies our group showed that etoposide, another topoisomarese II poison, causes irreversible damage to Sertoli cells. Thus, the aim of this study was to add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
26
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 74 publications
6
26
0
1
Order By: Relevance
“…Furthermore, DXR can induce chromosomal damage in the testis not only via oxidative stress but also by intercalation into DNA and disrupting topo-II-mediated DNA repair. It was also shown that DXR may induce enhanced testicular toxicity in prepubertal rats due to disruption of the supporting Sertoli cells (Brilhante et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, DXR can induce chromosomal damage in the testis not only via oxidative stress but also by intercalation into DNA and disrupting topo-II-mediated DNA repair. It was also shown that DXR may induce enhanced testicular toxicity in prepubertal rats due to disruption of the supporting Sertoli cells (Brilhante et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, our group has been showing that chemotherapeutic treatments during pre-puberty can lead to irreversible damage to the seminiferous epithelium of rats, although some degree of spermatogenesis restoration is frequently observed (Stumpp et al, 2004;Okada et al, 2009;Vendramini et al, 2010Vendramini et al, , 2012Brilhante et al, 2011Brilhante et al, , 2012. Among the chemotherapeutic drugs studied, etoposide (Stumpp et al, 2004;Okada et al, 2009) and doxorubicin (Vendramini et al, 2010(Vendramini et al, , 2012Brilhante et al, 2011Brilhante et al, , 2012 appear to be particularly aggressive to the reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…However, its harmful effects on other cells, such as spermatogonial stem cells (Tanigaki et al, 2013) and Sertoli cells (Brilhante et al, 2012), cannot be excluded when doxorubicin is administered during pre-puberty, because the spermatogenic damage is still observed in adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Sertoli cells play a key role in the control of spermatogenesis and in germ cell development (Fritz 1973, Carreau et al 1994 and any alteration in these cells can cause severe damage to spermatogenesis (Hess et al 1991, Brilhante et al 2012. However, there are very few studies about the effects of nicotine on late spermatogenesis (Lagunov et al 2011) in animals exposed during whole intrauterine (21-22 days in rats) period and lactation (from the birth to weaning).…”
Section: Introductionmentioning
confidence: 99%